Climate change and the world's river basins: anticipating management options. Issue 2 (1st March 2008) - Palmer, Margaret A; Reidy Liermann, Catherine A; Nilsson, Christer; Flörke, Martina; Alcamo, Joseph; Lake, P Sam; Bond, Nick
Abstract : Major rivers worldwide have experienced dramatic changes in flow, reducing their natural ability to adjust to and absorb disturbances. Given expected changes in global climate and water needs, this may create serious problems, including loss of native biodiversity and risks to ecosystems and humans from increased flooding or water shortages. Here, we project river discharge under different climate and water withdrawal scenarios and combine this with data on the impact of dams on large river basins to create global maps illustrating potential changes in discharge and water stress for dam‐impacted and free‐flowing basins. The projections indicate that every populated basin in the world will experience changes in river discharge and many will experience water stress. The magnitude of these impacts is used to identify basins likely and almost certain to require proactive or reactive management intervention. Our analysis indicates that the area in need of management action to mitigate the impacts of climate change is much greater for basins impacted by dams than for basins with free‐flowing rivers. Nearly one billion people live in areas likely to require action and approximately 365 million people live in basins almost certain to require action. Proactive management efforts will minimize risks to ecosystems and people and may be less costly than reactive efforts taken only once problems have arisen.